Evaluating mechanical properties of 100nm-thick atomic layer deposited Al2O3 as a free-standing film. (October 2020) - Koo, Junmo; Lee, Sangmin; Kim, Junmo; Kim, Dong Hwan; Choi, Byoung-Ho; Kim, Taek-Soo; Shim, Joon Hyung
Abstract: Due to the reduced thickness of thin films formed via atomic layer deposition, analyzing their true mechanical properties is difficult. To overcome this drawback, tensile tests on free-standing alumina thin films floating on water were conducted to measure their mechanical properties. Tensile tests on alumina thin films formed at different deposition temperatures were also conducted; the results indicated that higher Young's modulus and the strength were obtained from thin films formed at higher deposition temperatures. Factors responsible for the variations in mechanical properties were investigated through analyses of the structure, density, and composition of the films. Graphical abstract: Image, graphical abstract